ESTERIFIKASI CRUDE PALM OIL (CPO) MENGGUNAKAN KATALIS ZEOLIT ALAM TERAKTIFASI ASAM PADA PROSES PEMBUATAN BIODIESEL MELALUI METODE DUA TAHAP (ESTERIFIKASI-TRANSESTERIFIKASI) - Rahmiyati Kasim; Dwi Setyaningsih; Hery Haerudin (AGROINTEK, 2011)
Biodiesel, a renewable fuel is normally produced from refine oil and methanol in the presence of a catalyst; conventionally it is used a basic homogeneous catalyst. However, when oil with high amount of free fatty acid (FFA) is used, this catalyst should not be used with the aim to avoid the production soap. In this work, FFA present in crude palm oil (CPO) were esterified with activated natural zeolite catalyst. The esterification reaction was carried out 60oC, with a  23.41 : 1 molar ratio of methanol to CPO, reaction time of 170 minute and catalyst amount of 1.59 %, conversion FFA of CPO was 64.23 %. In this work, biodiesel yield achieved was around 71.97 %.Biodiesel, a renewable fuel is normally produced from refine oil and methanol in the presence of a catalyst; conventionally it is used a basic homogeneous catalyst. However, when oil with high amount of free fatty acid (FFA) is used, this catalyst should not be used with the aim to avoid the production soap. In this work, FFA present in crude palm oil (CPO) were esterified with activated natural zeolite catalyst. The esterification reaction was carried out 60oC, with a  23.41 : 1 molar ratio of methanol to CPO, reaction time of 170 minute and catalyst amount of 1.59 %, conversion FFA of CPO was 64.23 %. In this work, biodiesel yield achieved was around 71.97 %.